Navigating the brain and aging: exploring the impact of transposable elements from health to disease - Le Breton, Anna; Bettencourt, Margarida P.; Gendrel, Anne-Valerie (Frontiers in Cell and Developmental Biology, 2024)
Transposable elements (TEs) are mobile genetic elements that constitute on average 45% of mammalian genomes. Their presence and activity in genomes represent a major source of genetic variability. While this is an important driver of genome evolution, TEs can also have deleterious effects on the host. A growing number of studies have been focusing on the role of TEs in the brain, both in physiological and pathological contexts. In the brain, their activity is believed to be important for neuronal plasticity.In disease, such as neurological and age-related disorders, aberrant activity of TEs may play a role in the etiology of these pathologies, although this remains unclear. After a comprehensive overview of transposable elements and their interactions with the host, we review here the current understanding of the extent of TE activity in the brain, during the aging process, and in the context of neurological and age-related conditions.